STEM-7E Learning Cycle Learning Tools with Formative Assessment to Enhance Critical Thinking - Nukhba, Rania (Universitas Tidar, 2024)
Maximum learning requires planning and strategies in learning. This study aims to develop a learning tool product for dynamic fluid material based on STEM-7E Learning cycle with formative assessment to improve critical thinking skills of high school students. This research uses the research and development (R&D) method by following the stages of the 4D model and carried out until the develop stage. After the product was developed, the validity of the product was tested by two validators and 32 students of SMA Brawijaya Smart School Malang for the practicality test. The overall product validity test results were 100% and the product practicality test results were 98.25%. Based on the results of the validity and practicality tests, the developed product has a very valid and very practical category.